Mitochondria‐Associated Endoplasmic Reticulum Membranes in Human Health and Diseases - Yong Liu; Zi‐Hui Mao; Junwen Huang; Hui Wang; Xiao Zhang; Xin Zhou; Yue Xu; Shaokang Pan; Dongwei Liu; Zhangsuo Liu; Qi Feng (MedComm)
ABSTRACT As fundamental units of life activities, cells exhibit a high degree of structural refinement and functional specialization, forming the cornerstone of life complexity. Compartmentalization within cells is pivotal for maintaining the orderly progression of intracellular biochemical processes. Cellular compartments constitute the enclosed regions within the cytoplasm of all eukaryotic cells and are typically surrounded by a single or double layer of phospholipids, and include major organelles, such as the endoplasmic reticulum (ER) and mitochondria. Compartmentalization enables organelles to maintain distinct environments in terms of space, physics, and chemistry, thereby increasing their functionality. Human health is closely associated with cellular organelle homeostasis, and organelle dysfunction affects disease pathogenesis. In contrast to isolated cellular compartments, organelles are interdependent and communicate via membrane contact sites, with close membrane contact between the ER and mitochondria, forming mitochondria‐associated ER membranes (MAMs), which are involved in multiple cellular functions and whose integrity and function are essential for cellular homeostasis, with dysfunction implicated in various diseases. Investigating MAMs structure, function, and disease‐state alterations informs mechanisms and developing therapies. This article reviews the discovery, structure, function, and research progress of MAMs in human systemic diseases and cancer and explores their potential as therapeutic targets.